2021
DOI: 10.1002/ece3.8325
|View full text |Cite
|
Sign up to set email alerts
|

Effects of different types of low‐intensity management on plant‐pollinator interactions in Estonian grasslands

Abstract: This is an open access article under the terms of the Creat ive Commo ns Attri bution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 119 publications
0
3
0
Order By: Relevance
“…However, in the long term, an even more intense reduction in diversity can be observed, also impacting generalist species ( Burkle & Knight, 2012 ). Furthermore, the increase and lack of effect on nestedness in the 11 presented studies could be linked to the concentration of interactions by generalist species, both in plants and pollinators ( Jauker et al, 2019 ; Díaz Infante, Lara & Arizmendi, 2020 ; Morrison & Dirzo, 2020 ; Motivans Švara et al, 2021 ; Escobedo-Kenefic et al, 2022 ).…”
Section: Discussionmentioning
confidence: 87%
“…However, in the long term, an even more intense reduction in diversity can be observed, also impacting generalist species ( Burkle & Knight, 2012 ). Furthermore, the increase and lack of effect on nestedness in the 11 presented studies could be linked to the concentration of interactions by generalist species, both in plants and pollinators ( Jauker et al, 2019 ; Díaz Infante, Lara & Arizmendi, 2020 ; Morrison & Dirzo, 2020 ; Motivans Švara et al, 2021 ; Escobedo-Kenefic et al, 2022 ).…”
Section: Discussionmentioning
confidence: 87%
“…Additionally, it is important to assess which traits of flower morphology make plants important for pollinators in the SCNP plant-pollinator network, and likewise which traits of pollinators drive interactions. Analysis of functional traits in a plant-pollinator network can lead to a more complete understanding of how interactions are structured in a network (Motivans S ̌vara et al, 2021) and which traits are important to consider when introducing native plants. Our study takes a step towards this objective by analyzing subsets (functional groups) of species in the context of network structure and pollinator composition, but more intentional studies of functional traits could identify crucial trends in pollination that might illuminate patterns in different habitats.…”
Section: Figurementioning
confidence: 99%
“…It is thus critical to monitor plant-pollinator interactions and to understand the factors that cause these interactions to change across space and time. As many species of pollinating insects cannot be identified on sight, most studies quantifying plant-pollinator interactions capture insects that are observed to visit flowers and identifying them later using microscopy (e.g., Motivans Švara et al 2021; Rakosy et al 2022) or DNA barcoding (Creedy et al 2020). While these methods are accurate and can provide museum specimens that are valuable for a wide variety of research purposes (Rakosy et al 2023), they are time consuming, costly to scale, and require expert knowledge in insect taxonomy or barcoding.…”
Section: Introductionmentioning
confidence: 99%